Risk and fear of falls in the elderly of Campo Grande, Mato Grosso do Sul: sociodemographic and functional characteristics - Soares De Araújo, Hestela; Duarte Fantesia Costa Cruz, Arthur; Simionatto, Jaqueline; Carvalho Dos Santos Oliveira, Paola; Rosa Miziara Barbosa, Suzi (O Mundo da Saúde, 2020)
The carrying out activities of daily life and falls are factors directly related to quality of life, which can influence the independence and autonomy of elderly people. The objective of the study was to evaluate activities of daily living, risk and fear of falling in elderly people in Campo Grande, MS. This was a cross-sectional study, carried out with 32 elderly men and women, age ≥60 years and were participants in the Open University for the Elderly program, from April to September 2018. A Mini-Mental State Examination score ≥19 points was considered as the inclusion criterion. Instruments used were: Sociodemographic questionnaire; Katz index; Lawton-Brody scale; Downton scale that assesses the risk of falling and the Falls Efficacy Scale – International (FES-I-BRASIL) which assesses the fear of falling. According to the Katz Index, most elderly people were independent (84.4%). The Lawton-Brody Scale classified the majority of the elderly participants as independent (53.1%) and partially dependent (46.9%). On the Downton scale, the age group from 70 to 82 years old reached a score of (3.6±1.5) demonstrating a high risk of falling, at FES-I-BRASIL female elderly reached (25.6±6.6) points, showing a greater fear of falling. There was a relationship between the FES-I-BRASIL and Lawton-Brody scales (r=-0.443/ p=0.011), that is, the more thy carrying out crucial activities of daily living, the lower their concern is with falling. Elderly people in a more advanced age group have a higher risk of falling and female participants were more concerned about falling than their male peers.